Paul Feyerabend's irrational epistemology (Journal of Human Sciences, 2025)
This study aims to shed light on the irrational epistemology proposed by Paul Feyerabend, which has sparked widespread controversy in the philosophy of science circles. It is enough that it undermined the basic concept of scientific knowledge, which is the concept of the scientific method, as it denied the existence of a single method for science, considering that there are multiple methods that overlap in it. Feyerabend worked to end the dominance and authority of science over humanity, refusing to distinguish it from other human knowledge. He removed its sacred character, considering it merely a human product which is not different from other human knowledge and inventions. And he believes that contemporary science has become an ideology that has made humans hostage to it, as this ideology has entered their lives and restricted their freedom. Through his philosophy, Feyerabend worked to liberate humans from the new slavery by restoring respect for all human knowledge, which made his philosophy reflects a sublime human orientation. His philosophy contained a great deal of distinction, creativity, and originality, as it opened up new horizons and visions in the study of science and scientific phenomena.